WEB TEXNOLOGIYALARDÍŃ RAWAJLANÍW BASQÍSHLARÍ HÁM TÚRLERI - Mambetniyazov, M.T. (SCIENCE and SOCIETY, 2020)
The article discusses the stages of development of Internet technologies, in particular, Web-technologies, their role and importance in the educational process, and the differences between Web 1.0, Web 2.0, Web 3.0 technologies.